1998
DOI: 10.1242/jcs.111.16.2411
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic effects of the forced expression of HNF4 and HNF1α are conditioned by properties of the recipient cell

Abstract: Tagged versions of HNF4 or HNF1alpha cDNAs in expression vectors have been introduced by transient and stable transfection into three cell lines of hepatic origin that all fail to express these two liver-enriched transcription factors and hepatic functions. C2 and H5 cells are dedifferentiated rat hepatoma variants and WIF12-E cells are human fibroblast-rat hepatoma hybrids with a reduced complement of human chromosomes. Transfectants were analyzed for the expression state of the endogenous genes coding for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These findings thus further support a growth inhibitory role for FOXA1 in breast cancer. Cell‐type dependent transcriptional activity of FOXA proteins is not unique for breast cancer and has also been demonstrated in hepatoma and neuroblastoma cells 28, 29. Interestingly, another member of the FOX family, FOXO1 (also known as FKHR) also shows cell‐type dependent activity on the ER pathway: repression in HepG2 cells and activation in MCF‐7 cells 30, 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings thus further support a growth inhibitory role for FOXA1 in breast cancer. Cell‐type dependent transcriptional activity of FOXA proteins is not unique for breast cancer and has also been demonstrated in hepatoma and neuroblastoma cells 28, 29. Interestingly, another member of the FOX family, FOXO1 (also known as FKHR) also shows cell‐type dependent activity on the ER pathway: repression in HepG2 cells and activation in MCF‐7 cells 30, 31…”
Section: Discussionmentioning
confidence: 99%
“…Cell-type dependent transcriptional activity of FOXA proteins is not unique for breast cancer and has also been demonstrated in hepatoma and neuroblastoma cells. 28,29 Interestingly, another member of the FOX family, FOXO1 (also known as FKHR) also shows cell-type dependent activity on the ER pathway: repression in HepG2 cells and activation in MCF-7 cells. 30,31 Two global screens for ERa-responsive genes identified a role for FOXA1 in the activation of genes that contain both ERE and FOXA1 consensus sites in their promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…The self‐stimulation of HNF4α on its own promoter, and the reciprocal regulatory loop between HNF4α and HNF1α has been reported for more than two decades . This positive feedback loop between HNF4α and HNF1α needs a break, such as self‐inhibition of HNF1α, to sustain constant intracellular levels of HNF4α and HNF1α in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The self-stimulation of HNF4α on its own promoter, and the reciprocal regulatory loop between HNF4α and HNF1α has been reported for more than two decades. [18][19][20] This positive feedback loop between HNF4α and HNF1α needs a break, such as self-inhibition of HNF1α, 21 to sustain constant intracellular levels of HNF4α and HNF1α in vivo. Surprisingly, a following study indicated that HNF4α was capable of not only self-activating its own promoter, but also inducing a highly synergistic selfactivation in HeLa cells via interacting with HNF1α and HNF6.…”
mentioning
confidence: 99%